PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKTURAL THINK PAIR SQUARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIIIA SMP NEGERI 18 PEKANBARU - Lara Mulyana; Putri Yuanita; Atma Murni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is background based on mathematics learning outcomes in class VIIIA students of SMP Negeri 18 Pekanbaru which is still under Minimum Criteria of mastery learning that has been settled by the school that is 73. This type of research is the classroom action research with 2 cycles. The subject in this research were 16 male students and 22 female students with heterogeneous ability. The aims of this research are to improve the learning process and improve student’s mathematics learning outcomes in class VIIIA of SMP Negeri 18 Pekanbaru in odd semester of the 2017/2018 academic year based on KD 1.3 Understanding relations and functions and on KD 1.4 Determining the value of the function. The instruments of data collection were observation sheets that used to observe teacher and students activities during the learning process and students mathematic tests. The observation sheets were analyzed in descriptive narative, while the students mathematic tests were analyzed in statistic descriptive. Based on the data analysis of teacher and student activity after applying the cooperative learning model of Think Pair Square Structural Approach, teacher and student activities have done well and had an improvement at each meeting. Based on the data analysis of student learning outcomes, there is an improve in student learning outcomes in each cycle. Based on the analysis of KKM achievement, there were 8 students who reached KKM at UH 1 with percentage 21% and 21 students at UH 2 with percentage of 55,26%. Based on the result of research show that, there is an improve of students who get very high criteria and the decrease of students who get enough and low criteria. From this research it can be concluded that the implementation model of Think Pair Square structural approach can improve the learning process and also to improve student’s of mathematics learning outcomes in class VIIIA of SMP Negeri 18 Pekanbaru.Key words: Mathematics learning outcome, Cooperative learning, Think Pair Square, Class action research.